Analisis Yurisdis Perlindungan Hukum Nasabah Bank terhadap Kerahasiaan Bank di Indonesia - Zulfi Diane Zaini (Recital Review, 2019)
In order to avoid financial abuse, the customer made a special rule that prohibits banks to provide recorded information to anyone related to finance customers, deposits and its depositors except in certain cases mentioned explicitly in in the Banking Act. Based on such matters, the issues to be studied in this research is how the bank's efforts in maintaining the security of bank secrecy. Based on the research results revealed that public confidence on banking institutions to grow and thrive because in the presence of an element of the institution in the form of bank secrecy. Bank secrecy is everything related to finances and other things from the customer's bank in the ordinary course of banking should not be publicly disclosed to the public. The Banking Act Number 10 of Year 1998 has required the application of bank secrecy for the sake of maintaining public confidence in the banking institutions. But in practice it is still difficult to implement because there is no uniformity in the determination of categories including bank secrecy